THE ROLE OF MEMBRANE DISTILLATION IN REMOVAL OF MG2+ FROM DAIRY WASTEWATER - Ali A. Hasan (Mustansiriyah University/College of Engineering, 2021)
The dairy industry has become a great source of human development in terms of providing the necessary amount of energy and calories, in addition to the vitamins needed to sustain life. Iraq is one of the largest countries that are dairy-producing and it is expected that the average per capita consumption of dairy products will increase from 52 litres to more than 60 litres during the next three years, then to more than 90 litres by 2025. Dairy production needs to consume large quantities of water It needs to consume 2-6 cubic meters of water to produce one ton of milk. These large quantities of water will lead to the discharge of large amounts of wastewater, which may reach 70% of the water used. Over the years I have used various techniques and methods for treating dairy wastewater. In this study, the membrane permeation removal technique (MD) was used to find out how efficient this technique is in removing the magnesium ion from the milk laboratory wastewater. The results came with the possibility of this technique in removing a small percentage of up to 9.76% at a temperature of approximately 45 degrees Celsius, which is a small percentage compared to the concentration of the interior and the effort exerted. For this reason, it is not recommended to use this mechanism to remove magnesium from dairy wastewater.